Morfologia verbale dei dialetti lombardi nord-orientali nel loro contesto geolinguistico - Rührlinger, Brigitte (Editions de Linguistique et de Philologie, 2015)
Based on dialect data of the Linguistic atlas of Dolomitic Ladinian and neighbouring dialects, 2nd part this survey tries to offer a description as complete as possible of the verbal morphology of the north-eastern Lombard dialects, including aspects of phonetics and morphosyntax and, in this way, to find explanations for a number of phenomena which have not been considered yet. The qualitative description of the verbal morphology of this dialect area with its rich variation is combined with quantitative results of dialectometry, which specify and complete the traditional division of the dialect area research and provide a new prospect of the dialects analysed within their geographic embedding.